Geographic variation in the use of triptans and opioids for the acute treatment of migraine attacks. Issue 10 (28th November 2021) - Lee, Jae Hyun; Shewale, Anand R.; Barthold, Douglas; Devine, Beth
Abstract: Objective: To assess the geographic variations in triptan and opioid prescribing patterns for patients with migraine. Background: Numerous guidelines recommend triptans as the standard of care for migraine attacks, yet opioids are still widely used for migraine treatment. Variation in the use of opioids and triptans for the treatment of migraine by geographic location is not well known. Methods: Using a US claims database, we conducted a retrospective cohort study of adults diagnosed with migraine between 2016 and 2018. We used a 12‐month follow‐up period to assess triptan and opioid utilization, stratified by the nine Census Bureau‐designated divisions. To examine the geographic factors that affect triptan and opioid use among patients, we conducted two sets of multivariable analyses. First, we analyzed the odds of a patient being a triptan or opioid user in the follow‐up period, defined as ≥1 triptan or opioid claim. We then analyzed the medication use rate among triptan or opioid users. Results: Overall, we had a final study population of 113, 921 patients. In the follow‐up period, 52.9% (60, 247/113, 921) [range: 48.0%–56.3%] of patients were triptan users and 41.0% (46, 708/113, 921) [range: 28.9%–48.4%] of patients were opioid users with significant differences across census divisions ( p  < 0.001). Triptan users had a mean (SD) of 4.8 (4.7) triptan claims annually with no significant differences across divisions ( p  = 0.188). Opioid users had a mean (SD) of 5.4 (6.8) opioid claims annually with significant differences across divisions ( p  < 0.001). The observed variation in opioid use stemmed from the proportion of patients using opioids in each region and not from the number of opioid prescriptions per user. Conclusions: There was a significant geographic variation in the use of opioids and to a lesser degree the use of triptans. The widespread use of opioids and the large variation in use other than triptans as the standard of care suggest that improvements could be made in the acute treatment of migraine attacks.